Studi Penyembuhan Luka Insisi secara In Vivo Menggunakan Ekstrak Daun Kayu Manis (Cinnamomum burmannii) pada Tikus Putih Jantan - Fathnur Sani Kasmadi; Nada Afrilia; Diah Tri Utami; Yuliawati Yuliawati (Fakultas Farmasi Universitas Pancasila, 2022)
Cinnamon leaves are traditional plants that contain secondary metabolites such as flavonoids, tannins, saponins, alkaloids, and phenols. All of these compounds play an essential role in the wound healing process. This study aimed to determine the effects of cinnamon (Cinnamomum burmannii) on incision wound healing in male rats. The research method used a post-test only control group design approach that uses five treatment groups: positive control (Bioplacenton® Gel), negative control (Vaseline flavum), and ethanol extract of cinnamon leaves at concentrations of 10%, 20%, and 30%. The results showed that the ethanol extract of cinnamon leaves affected wound healing, as observed from the day of wound healing, the AUC length of the wound, and levels of hydroxyproline. The statistical test results showed a significant difference between the groups (p<0.05), where the best concentration was 30%, followed by 20% and 10%. Therefore, we concluded that the ethanolic extract of cinnamon leaves can heal wounds in male rats.